2018
DOI: 10.1021/acs.biochem.8b01077
|View full text |Cite
|
Sign up to set email alerts
|

Shutting Down Shigella Secretion: Characterizing Small Molecule Type Three Secretion System ATPase Inhibitors

Abstract: Many important human pathogens rely on one or more type three secretion systems (T3SS) to inject bacterial effector proteins directly into the host cell cytoplasm. Protein secretion through the needle-like type three secretion apparatus (T3SA) is essential for pathogen virulence and relies on a highly-conserved ATPase at the base of the apparatus, making it an attractive target for anti-infective therapeutics. Here, we leveraged the ability to purify an active oligomeric Shigella T3SS ATPase to provide kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Each of the Spa47 constructs encoded in pTYB21 were transformed into E. coli Tuner (DE3) cells and were expressed and purified as previously described [22,29,30]. Briefly, the expression strains were grown to an OD 600 of approximately 0.8 in Terrific Broth medium containing 0.1 mg/ml ampicillin at 37˚C and 200 RPM.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Each of the Spa47 constructs encoded in pTYB21 were transformed into E. coli Tuner (DE3) cells and were expressed and purified as previously described [22,29,30]. Briefly, the expression strains were grown to an OD 600 of approximately 0.8 in Terrific Broth medium containing 0.1 mg/ml ampicillin at 37˚C and 200 RPM.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…103 Case et al (2018) identified 3 non-competitive inhibitors of Spa47 (SctN of Shigella flexneri) through virtual screening techniques and were predicted to bind at the interface between protomers based on modelling the oligomeric structure of Spa47 after a heterohexameric F-type ATPase. 105 Two inhibitors functioned in vivo, exhibiting almost no secretion without compromising S. flexneri or HeLa viability. All three compounds exhibited inhibition of the ATPase.…”
Section: Inhibitor Classes and Their Associated Mechanism Of Inhibitionmentioning
confidence: 99%
“…The authors note that IpaD is still present in needle complexes, suggesting that the inhibitors are inhibiting secretion, potentially via an ATP dependent manner. 105 New knowledge from the recent cryo-EM structure of homohexameric EscN (SctN of EPEC discussed above) may assist with a more targeted approach to drug design against the ATPase. 18 Phenoxyacetamide inhibitors have previously exhibited inhibitory properties towards the T3SS, with a few compounds displaying high nanomolar IC 50 values.…”
Section: Inhibitor Classes and Their Associated Mechanism Of Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that the Shigella protein Spa47 is a T3SS ATPase whose activity is essential for protein secretion through the apparatus and overall Shigella virulence . Furthermore, Spa47 oligomerization is required for ATPase activity, as residues from opposite sides of adjacent Spa47 protomers contribute to interfacial active sites within the complex, making Spa47 oligomerization a likely means of regulating T3SS activity in vivo and an attractive target for nonantibiotic therapeutics against Shigella infections …”
Section: Introductionmentioning
confidence: 99%